PENGEMBANGAN MEDIA PEMBELAJARAN POSTER TERINTEGRASI AL-QUR’AN DAN SAINS DENGAN MENGGUNAKAN APLIKASI CANVA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Hidayatullah, Alva; Firdaus, Firdaus; Muntaha, Darul (BIOCHEPHY: Journal of Science Education, 2024)
The purpose of this thesis is to: 1) Assess the validity of the integrated learning media in the form of posters that combine science and the Qur'an using the Canva application to improve student learning outcomes; 2) Assess the usefulness of the integrated learning media in the form of posters that combine science and the Qur'an using the Canva application to improve student learning outcomes; and 3) Assess the effectiveness of the integrated learning media in the form of posters that combine science and the Qur'an using the Canva application to improve student learning outcomes. The PLOMP model is used in this thesis to conduct research of the Research and Development (R&D) type. Observation, testing, questionnaire distribution, and documentation are some of the methods used to collect data. Primary and secondary data (books about the Solar System, research books, papers, websites, and previous studies) are the sources of data in this research. The instruments used in this study include the module validity questionnaire, the practicality questionnaire, and the effectiveness questionnaire. To evaluate the effectiveness of the product and the improvement of student learning outcomes, data analysis approaches used include product validity analysis, product practicality analysis, normality analysis, homogeneity analysis, t-test analysis, and N-Gain test analysis. Using the Canva application, the research findings developed an integrated learning medium in the form of science and Qur'an posters to enhance student learning outcomes. The research findings indicate that: 1) The integrated learning media in the form of posters that combine science and the Qur'an with the aid of the Canva application is valid for use in educational activities; 2) The integrated learning media in the form of posters that combine science and the Qur'an with the aid of the Canva application is practical for use in educational activities; 3) The integrated learning media in the form of posters that combine science and the Qur'an with the aid of the Canva application is effective in improving student learning outcomes, as measured by the t-test and N-Gain test. This demonstrates a change in the learning objectives of the students before and after they used the developed module. Furthermore, an improvement in student learning outcomes is indicated by the average percentage score of the pre-test and post-test results, which increased from 37.18 to 82.81.